PERCEIVING BOUNDARIES IN UNFAMILIAR TURKISH MAKAM MUSIC: EVIDENCE FOR GESTALT UNIVERSALS? - (:unkn) unknown (UNIV CALIFORNIA PRESS, 2017)
MUSIC SEGMENTATION IS A WIDELY RESEARCHED topic within music perception. Even though there is extensive data on the role of surface structure features and music training (e.g., Deliege, 1987) in segmentation, not much is known yet about the influence of implicit knowledge-based features acquired through musical enculturation. The goal of our study was to fill this gap. Makam music-trained musicians, nonmusicians, and Western listeners marked their segmentations online as they listened to mostly 19th century, unfamiliar Turkish makam tunes, all recorded in a Qanun timbre on MIDI with retained microtonal structure. In addition, two experts segmented the tunes in a free-time setting. We found considerable within- and across-group agreement, as well as good agreement with the expert segmentations. After transforming each participant's segmentations into hits and false alarms based on their match or mismatch with expert segmentations, we observed that musicians overlapped significantly more with expert segmentations than do the other two groups. Segmentations in all three groups were strongly driven by mostly local surface features. Overall, our results are more supportive of a universality claim as proposed by the Gestalt school of psychology than an enculturation claim.
Keywords: music segmentation; makam music; Gestalt; music training; music enculturation; CROSS-CULTURAL ERP; MELODIC SEGMENTATION; PERCEPTION; LISTENERS; LERDAHL; RULES; TIME